2011
DOI: 10.1177/1049909111406900
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Antimicrobial Use for Palliative Care In-Patients During the Last Week of Life

Abstract: The current practice of antimicrobial prescribing, especially for patients who are eminently dying, may need to be reviewed. Initiation of antimicrobial treatment in this group of patients should be based on clear treatment goals and desired outcomes, considering views of patients and families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 9 publications
0
13
0
3
Order By: Relevance
“…More remarkable is that even when overall goals of care shifted to comfort care, the use continued in more than one third of patients. Although the issue of antimicrobial use at the end of life has been addressed by other investigators, 1,6,7,1214 this study is unique in its description of antimicrobial use among a cohort of patients with advanced cancer in an acute care setting.…”
Section: Discussionmentioning
confidence: 99%
“…More remarkable is that even when overall goals of care shifted to comfort care, the use continued in more than one third of patients. Although the issue of antimicrobial use at the end of life has been addressed by other investigators, 1,6,7,1214 this study is unique in its description of antimicrobial use among a cohort of patients with advanced cancer in an acute care setting.…”
Section: Discussionmentioning
confidence: 99%
“…Všichni, kteří měli potvrzenou infekci, dostávali antibio tika, z nich 75,6 % do dne úmrtí [10]. Na pacienty v posledním týdnu života se zaměřili Abduh Al-Shaqi et al, kteří retrospektivně hodnotili záznamy 138 pacientů zemřelých na specializované paliativní jednotce [11]. Z nich bylo 63 % léčeno jedním nebo více antimikrobiálními léky, 31,3 % mělo více než jedno antibio tikum, nejčastěji na infekce dutiny ústní ( (14,3 %).…”
Section: Discussionunclassified
“…Vysoké procento pacientů bylo zároveň léčeno až do úmrtí. Ve studii Nakagawy et al 19,7 %, Stiela et al 44 % a v posledním týdnu života bylo léčeno 63 % pacientů ve studii Al-Shaqiho et al [11,12,15]. Aplikační cesty antibiotik se opět liší dle místa studie.…”
Section: Defi Nice Infekce Paraneoplastická Horečka a Indikátory Atbunclassified
“…Time between last chemotherapy and death (TLCD) can also be compromised by a lack of skill in palliative care and was found in KSA to be shorter than the world average, therefore indicating aggressive end of life care (Karim et al, 2015). Similarly, Al-Shaqi et al (2012) found that the use of antimicrobials was too liberal in patients approaching death, again indicating aggressiveness of end of life care.…”
Section: Issues and Problemsmentioning
confidence: 99%